2009
DOI: 10.1007/s11033-009-9508-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense of betaine against isoprenaline-induced myocardial infarction in rats

Abstract: We investigated the antioxidant preventive effect of betaine on isoprenaline-induced myocardial infarction in male albino rats. Isoprenaline induced myocardial infarction was manifested by a moderate elevation in the levels of diagnostic marker enzymes (alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase and creatine phosphokinase) and homocysteine in plasma of experimental rats. Significant rise in the level of lipid peroxidation with a concomitant decline in the levels of myocardial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 39 publications
8
36
1
Order By: Relevance
“…This is consistent with an earlier study (Farvin et al 2006) which also indicated that lipid peroxidation is a key factor in the pathogenesis of isoprenaline-induced myocardial infarction. The enhanced lipid peroxidation in heart lysosomes of isoprenaline-administered rats might have been due to the reduction in tissue antioxidant defense status, as reported earlier (Ganesan et al 2008b).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This is consistent with an earlier study (Farvin et al 2006) which also indicated that lipid peroxidation is a key factor in the pathogenesis of isoprenaline-induced myocardial infarction. The enhanced lipid peroxidation in heart lysosomes of isoprenaline-administered rats might have been due to the reduction in tissue antioxidant defense status, as reported earlier (Ganesan et al 2008b).…”
Section: Resultssupporting
confidence: 71%
“…It has been shown that betaine regulates erythrocyte (red blood cell) membrane ATPases via conformational changes, which results in cell volume control (Moeckel et al 2002). Earlier, we reported the protective effect of betaine on antioxidant status (Ganesan et al 2008b), mitochondrial function (Ganesan et al 2007a), protein and glycoprotein metabolism (Ganesan et al 2007b), and lipid metabolism (Ganesan et al 2008a) in isoprenaline-induced myocardial infarction in Wistar rats. In the present study, an attempt was made to assess the protective effects of betaine on isoprenaline-induced myocardial infarction with respect to changes in the levels of lysosomal enzymes and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 93%
“…The glutathione antioxidant enzymatic system plays an important role in cellular defense against reactive oxygen species (ROS) (Alirezaei et al, 2012). Glutathione peroxidase (GPx) and superoxide dismutase (SOD), which are responsible for the destruction of peroxides, have specific roles in protecting tissues from oxidative damage (Sun et al, 2008;Ganesan et al, 2011). A reduction in the activity of these enzymes may lead to the formation of O 2 -and H 2 O 2 when birds experience oxidative stress, which in turn can lead to increased hydroxyl radical formation with harmful consequences (Kalra et al, 1988).…”
Section: Blood Parametersmentioning
confidence: 99%
“…Evidence, here provided, that the in vitro endothelial beneficial effect of GabaBet against the hGluc detrimental effects occurs through the positive regulation of SIRT1 and negative modulation of p16 INK4A indicate that this betaine display effects similar to those elicited by stachydrine, 18,29 suggesting its potential role as natural bioactive compound in the prevention of hyperglycaemia-induced endothelial dysfunction. A deeper characterization of the metabolism and the molecular mechanism(s) of action of this betaine is critical to understand the differences with GabaBet intermediate in gut microbial metabolism of Lcarnitine to TMAO.…”
Section: Discussionmentioning
confidence: 74%